Anopheles mortality is both age- and Plasmodium-density dependent: implications for malaria transmission. - Dawes, E; Churcher, T; Zhuang, S; Sinden, R; Basáñez, MG (2009)
BACKGROUND: Daily mortality is an important determinant of a vector's ability to transmit pathogens. Original simplifying assumptions in malaria transmission models presume vector mortality is independent of age, infection status and parasite load. Previous studies illustrate conflicting evidence as to the importance of Plasmodium-induced vector mortality, but very few studies to date have considered the effect of infection density on mosquito survival. METHODS: A series of three experiments were conducted, each consisting of four cages of 400-1,000 Anopheles stephensi mosquitoes fed on blood infected with different Plasmodium berghei ookinete densities per microlitre of blood. Twice daily the numbers of dead mosquitoes in each group were recorded, and on alternate days a sample of live mosquitoes from each group were dissected to determine parasite density in both midgut and salivary glands. RESULTS: Survival analyses indicate that mosquito mortality is both age- and infection intensity-dependent. Mosquitoes experienced an initially high, partly feeding-associated, mortality rate, which declined to a minimum before increasing with mosquito age and parasite intake. As a result, the life expectancy of a mosquito is shown to be dependent on both insect age and the density of Plasmodium infection. CONCLUSION: These results contribute to understanding in greater detail the processes that influence sporogony in the mosquito, indicate the impact that parasite density could have on malaria transmission dynamics, and have implications for the design, development, and evaluation of transmission-blocking strategies.